A carrier-free nanoparticle with dual NIR/acid responsiveness by co-assembly of enediyne and IR820 for combined PTT/chemotherapy. Issue 19 (5th May 2021) - Lu, Haotian; Wang, Wenbo; Li, Xiaoxuan; Zhang, Mengsi; Cheng, Xiaoyu; Sun, Ke; Ding, Yun; Li, Xinxin; Hu, Aiguo
Abstract : Combined photothermal therapy/chemotherapy by co-delivery of a photosensitizer (PS) and a chemotherapeutic drug has demonstrated great potential for cancer treatment. Abstract : Combined photothermal therapy/chemotherapy by co-delivery of a photosensitizer (PS) and a chemotherapeutic drug has demonstrated great potential for cancer treatment. The intrinsic drawbacks of traditional drug delivery systems (DDSs), such as tedious synthetic procedures, side effects originated from the carrier materials, low loading efficiency, and uncontrolled drug release, however, have impaired their further advancement. On the other hand, enediyne antibiotics are highly cytotoxic toward cancer cells through the generation of lethal carbon radicals via thermal-induced cyclization, endowing them with great potential to achieve enhanced synergistic anticancer performance by incorporation with the photothermal effect of PS. To this end, a carrier-free and NIR/acid dual-responsive DDS was constructed for combined photothermal therapy/chemotherapy. The facile co-assembly of maleimide-based enediyne and PS IR820 was achieved in aqueous solution to give nanoparticles (EICN) with a hydrodynamic diameter of 90 nm and high stability. In vitro study confirmed the acid/NIR dual-responsive degradation and drug release, free radical generation and DNA-cleaving ability of EICN, which was accomplished by the corporation of enediyne and IR820 moieties. Further tests on HeLa cells verified the excellent synergistic anticancer performance of EICN including the improved cellular uptake, NIR-enhanced drug release, DNA damage and histone deacetylase inhibitor capacity. Overall, this carrier-free DDS with dual acid/NIR-responsivity would potentially provide new insights for the development of combined photothermal/chemotherapy.